Synthesis and Molecular Docking Study of Pyrazine-2-carboxylic acid Derivatives. Issue 1 (May 2020) - Zulqurnain, Muhammad; Ghulam Fahmi, M. Riza; Fadlan, Arif; Santoso, Mardi
Abstract: The pyrazine-2-carboxylic acid derivatives 1a-c with aromatic, cyclic, and aliphatic side chain were successfully synthesized. The structures of derivatives were confirmed by spectroscopic methods (FTIR, NMR, HRMS). The molecular docking was performed to determine the possible binding interaction between 1a-c with Mycobacterium tuberculosis InhA protein. The derivative 1c showed the lowest rerank score (-86.4047 kcal mol −1 ) and it might correspond to the lowest experimental MIC value.